Finding forever with the firefighter - Heaton, Louisa (Harlequin medical romance., 2024)
While rescuing patients, paramedic Addy faces hazardous situations every day. Yet after the devastating loss of her family, she refuses to endanger her heart. When she meets dedicated firefighter and single dad Ryan, the flame of attraction that ignites is absolutely unwanted—and completely undeniable! But Ryan’s resolved to protect his daughter from anyone else leaving her, and even Addy admits she’s a relationship flight risk. So instead of finding forever together, they should ignore that sizzling spark…right?